Chitosan/aminoacid hydrogels with antimicrobial and bioactive properties as new scaffolds for human mesenchymal stem cells culture applicable in wound healing - M. Piatkowski; D. Kitala; J. Radwan-Praglowska; L. Janus; A. Klama-Baryla; W. Labus; E. Tomanek; J. Glik; D. Matysek; M. Kawecki (eXPRESS Polymer Letters)
Application of human mesenchymal stem cells brings a new hope for advanced wound healing. To enable cells culture and their viability maintenance, a new type of biomaterials must be developed. Scaffolds prepared from polymers of natural origin can mimic extracellular matrix. Chitosan, which is a chitin derivative, has many favorable properties like biodegradability or lack of cytotoxicity. Therefore, it is widely applied in medicine and pharmacy. Nevertheless, its chemical modification may lead to the loss of biocompatibility of the material and generate some significant problems with cells culture. In this article a novel strategy of the bioactive and antimicrobial chitosan hydrogel scaffolds is presented. As crosslinking agents non-toxic substances were used such as aspartic acid and glutamic acid. Obtained biomaterials were investigated over their chemical structure, morphology and biological activity. Performed tests using human mesenchymal stem cells confirmed bioactivity and biocompatibility, as well as antibacterial and antifungal properties.